Vibro-acoustic Performance of Different Steel Studs in Double-leaf Walls by Finite Element Analysis. Issue 2 (June 2015) - Nguyen, Bac; Morgan, Tertia; English, Martin; Castellucci, Michael
Cold-formed steel studs are often used in lightweight partition walls to provide structural stability but in the same time they change the acoustic performance of the whole system. The overall design of such lightweight structures for acoustic sound insulation becomes very complicated as the sound passing through stud needs to be quantified. One of the greatest challenges is to characterize the stud's geometric effects on the sound transmission of the partition walls. This paper presents a 2-D Finite Element modelling approach and results into the vibro-acoustic performance of different studs in double-leaf walls which are placed in between a reverberant source room and a receiving room. The acoustic medium inside rooms was modelled using fluid elements and the structure was modelled with plane strain elements. The interaction between the acoustic medium and the structure was modelled in a coupled structural-acoustic analysis. An FE modelling setup which includes appropriate model parameters to be used in the structural-acoustic analysis was presented. The FE sound reduction of double-leaf walls using two different stud profiles was then calculated. Experimental tests complying with standards ISO 717-1:1997 and 140-3:1995 were also carried out to evaluate the FE results. It has shown that the stud's shape have significant effects on the sound reduction of the double-leaf walls, and the FE results have similar trends are in fair agreement with the experimental results. A parametric study was conducted and the effects of the stud's shapes on the sound reduction were presented and discussed.